A practical guide to dragon magic - Morris, Susan J. (Renton, WA : Wizards of the Coast, 2010)
Discusses the magical properties and secrets of dragons from the world of Dungeons & Dragons, focusing on the details of the Darastrix Academy, where hatchlings live and learn alongside young wizards.
"Dungeons & dragons"--Cover.
6.9
3-6.
3-6
Keywords: Dragons -- Juvenile literature; Dragons; Dragons